A educação ambiental como ferramenta da gestão participativa na microbacia do Rio Cambucais, Silva Jardim, RJ - Kobata, Cláudia (2009)
The Environmental Education has been considered to be one of the most important tools for the Brazilian environmental policy, since it involves procedures, whose the individual and the collective build up social values, knowledge, cleverness, attitudes and abilities for the environment conservation. This construction demands a large participation from the many sectors of the society. The Law on Water Resources recommends that the management of these resources should require integration, decentralization and community participation to insure Participant management. In this way, the rules on water conservation and the precepts aiming environmental education can be associated. The Consórcio Intermunicipal Lagos São João (CILSJ), as an instrument for management of the environmental policy and of the water resources, uses environmental education in the procedures of participant management of the river basins in which it is inserted. The study intends to analyze environmental education as a procedure that promotes an improvement in the environmental quality of the Cambucaes River s micro basin, city of Silva Jardim, state of Rio de Janeiro, based on the Communities in Action on the Micro Basins Project (Projeto Comunidades em Ação nas Microbacias), idealized by the CILSJ in its Environmental Education Program. A qualitative methodology was used, in a descriptive research, hoping to reveal the thoughts and actions of the individuals involved in this study, about their comprehension and attitudes for the improvement in the environmental quality of their area. Thus, beyond the preliminary studies of the area and technical visits, in the fieldwork questionnaires were applied to teachers (twenty four in two phases) and students (four hundred and twenty nine also in two phases) of two schools in the Cambucaes River s micro basin. The analysis of these data revealed the profile of the target public about it s environmental perception and promoted the evaluation of the effects of the environmental education over this public s thoughts and attitudes, promoters of a participant action in the community.